Incorporation of different physical forms of fat replacers in the production of low-fat/reduced-fat meat products: which is more practical? - Asyrul-Izhar, Abu Bakar; Bakar, Jamilah; Sazili, Awis Qurni; Goh, Yong Meng; Ismail-Fitry, Mohammad Rashedi (Taylor & Francis, 2022)
This review details the different approaches to replacing animal fat used in meat products with non-animal fat ingredients based on their physical forms during processing. Six different physical forms to replace the fat are categorized as 1) powder, 2) paste, 3) plant oils, 4) combinations of dietary fiber with plant oils or animal protein/skin, 5) pre-treated fat replacer, and 6) oleogel and emulsion gels. The ingredients, characteristics, processes, mechanisms, advantages, and disadvantages of all the fat replacers are discussed extensively. The oleogel and emulsion gel approach is found to be the most practical by retaining the solid-like properties while possessing a healthier fatty acid profile over other approaches. This approach also can solubilize both hydrophobic and hydrophilic components and also have good thermodynamic stability, thus imitating the animal fat. In addition, the cost of production is kept low while maintaining the nutritional attributes, physicochemical and sensorial properties of meat products.